Justine cooks : recipes (mostly plants) for finding your way in the kitchen - Doiron, Justine (Clarkson Potter/Publishers, 2024)
"In her debut cookbook, social media storyteller and food influencer Justine Doiron shares how to find your cooking style through 100 approachable and innovative recipes. Known for her love of vegetables, beans, bread, farmers' markets, and her dog Walter, social media cooking star Justine Doiron turned her hobby of cooking into her creative outlet in her early twenties when she began sharing her recipes and experiences with food on TikTok and Instagram. Over the course of five years, she has found her culinary style as well as the confidence to cook intuitively and create her own unique but unfussy dishes like Baked Kale Salad, Lime-Roasted Cabbage with Turmeric White Bean Mash and Tiny Salted Tiramisu Cookies. In this collection of 100 recipes that highlight her loves of vegetables, tofu, and seafood, home cooks will find the kind of wonderfully original and delicious recipes Justine is known for such as ACV Brussels Sprouts with Toasted Cornmeal, Basil Cucumbers with Slightly Sweet Peanuts, and Parmesan-Crusted Butter Beans. Chapters include snacks like Turmeric Popcorn & Croutons, staples like Crispy, Craggily Croutons and Shimmery, Peppery Hot Sauce, plus mornings, salads, proteins, and more. With these recipes, Justine hopes to teach home cooks how to become more confident through basic techniques along, tips, helpful guides, and lots of encouragement. More than a collection of delicious recipes, Untitled is an invitation to embrace experimentation and creativity in the kitchen"--